The Effect of Zig-Zag Run and Shuttle Run Training on the Agility of Crescent Kicks of Pencak Silat Athletes in Teluk Jaya Village, Kelekar District - Dwindi Rusdiani; Andi Rahman; Jujur Gunawan Manullang; Muhsana El Cintami Lanos (Universitas Negeri Semarang, 2026)
The problem in this study is the low agility of the sickle kick of pencak silat athletes at the school in Teluk Jaya Village, Kelekar District. Therefore, during the match, the attacks carried out are easily read and analyzed by the opponent. The purpose of this study was to determine the effect of zig-zag run and shuttle run training on the agility of the sickle kick of pencak silat athletes in Teluk Jaya Village, Kelekar District. The method used was an experimental study with a two-group pretest–posttest design. This research design aims to determine the causal relationship or the effect of a treatment on the dependent variable. The population of this study was all 20 pencak silat athletes, with 16 training sessions in each group. The sample of this study was divided into two groups, each consisting of 10 teenage boys. The data collection instrument in this study used a test, namely the sickle kick agility test. The test was conducted twice, namely a pretest where the aim was to determine the level of the athlete's initial ability before being given treatment, and a posttest after the zig-zag run and shuttle run training treatment. The data is in the form of the average number of crescent kicks successfully performed in a certain time according to the Bruce kick agility test procedure. The data analysis techniques used consist of descriptive statistical analysis and inferential statistics. Descriptive analysis uses the mean test of pretest and posttest results by processing the data results from each group. Inferential analysis with prerequisite tests uses normality tests and homogeneity tests. The data results are continued with an independent sample t-test to determine the effect of zig-zag run and shuttle run training on the crescent kick agility of pencak silat athletes.